Leukemia Cutis - Amraoui Nissrine; Gallouj S; Meziane M; Mernissi F (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2015)
A patient of 55 years presented seven days ago a fever. Since 3 days he developed multiple nodular lesions. Dermatological examination revealed pruriginous pinkish and infiltrated plaques, nodules and papules, with firm consistency, disseminated on the trunk .There was no mucosal or nail lesions. The rest of the physical examination was normal. Histology was in favor of leukemia cutis witch correspond to cutaneous localization of acute leukemia. The study of skin lesions allowed a quick diagnosis of the etiology of fever. The care of his leukemia is accompanied by the disappearance of lesions.